Implementasi Alat Evaluasi Menggambar Busana di SMK Swasta Kelompok Pariwisata Kabupaten Sleman - Sri Widarwati; Emy Budiastuti; Prapti Karomah (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objectives of the study were to determine the application procedure of the evaluation instrument of fashion drawing, to analyse the consistency of the evaluation results, and to determine the communicative reporting procedure of the evaluation results in the Department of Tourism of Vocational High Schools in Sleman regency, Yogyakarta. This study was categorised into a survey study. The population of this study were teachers and students. There were 30 samples selected with purposive sampling. There were six teachers as the assessors. The data collection techniques used consistency assessment instruments by examining the index of reliability. The report of the results of Drawing Fashion Design assessment was shown in the profile of the students. The data was analysed using quantitative descriptive with percentages. The consistency of the assessment was examined using cronbach alpha analysis. While the reporting procedure was analysed descriptively based on the calculation of the final score. The results of the study were the application procedure of the evaluation instrument that is started with the preparation of the teachers to provide the assessment instruments that includes the materials, the grid, the test items and the rubric. Based on the criteria, it is in the very good category with a mean score of 56.83. The consistency of the assessment results is in a good category with a mean score of 0,800. Based on the competency profile, The mean score of the students’ assessment result was 77, 3. With the minimum score of 70, it was proved that all of the samples of this study were categorised into competent in fashion drawing.